Political economy of Japanese and Asian development - Ichimura, Shinichi (ISEAS, 1998)
The modern economic growth of Japan since the time of the Meiji Restoration in 1868 presented a new challenge to the Western world. Over the past 150 years she has demonstrated that successful performance in economic and political development of a non-Western nation is possible. Moreover, Japan has risen from the poverty-stricken feudal conditions in the Edo period to the prosperous modern or post-industrial society in only several generations.